Bio-hydrometallurgy dynamics of copper sulfide-minerals probed by micro-FTIR mapping and Raman microspectroscopy - Adamou, Anastasia; Nicolaides, Antonis; Varotsis, Constantinos (My University, 2019)
We report the μm-FTIR mapping and Raman microspectroscopic detection of bornite [Cu5FeS4]-, chalcocite [Cu2S]-, and covelitte [CuS]- bacterial interactions by a consortium of microorganisms consisted of Acidithiobacillus ferrooxidans, Acidithiobacillus thiooxidans, Acidithiobacillus caldus, Leptospirillum ferriphilum, Leptospirillum ferroodiazotrophum and Sulfobacillus thermosulfidooxidans. The absorption signals of amide I, K+-jarosite [KFe3(SO4)2(OH)6] and of the produced extracellular polymeric substances (EPS) from the mixed culture as a function of position on the surfaces of the bioleached bornite, chalcocite and covellite demonstrated their heterogeneity within the surface of the minerals. This reveals the high level of biofilm, EPS, and jarosite biosynthesis on the surface of the minerals and might explain why they associate. To our knowledge this is the first combined application of μm-FTIR mapping and Raman microspectroscopy for the bioleaching behaviour of bornite, chalcocite and covellite and the comparison with other bioleached systems such as chalcopyrite [CuFeS2] provides valuable information on the whole bio-hydrometallurgy Cu/Fe/S system. Both techniques provide spectrally rich, label-free, nondestructive visualizations of the bio-hydrometallurgy dynamics of copper sulfide minerals for processing and storage of large spectral data sets which are valuable for evaluation of copper containing minerals.
Keywords: Biofilm formation; Jarosite biosynthesis; Copper sulfide minerals; Micro-FTIR mapping; Raman